2012
DOI: 10.1002/path.4056
|View full text |Cite
|
Sign up to set email alerts
|

Use of mutation profiles to refine the classification of endometrial carcinomas

Abstract: The classification of endometrial carcinomas is based on pathological assessment of tumour cell type; the different cell types (endometrioid, serous, carcinosarcoma, mixed, and clear cell) are 11 Corresponding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
235
3
22

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(283 citation statements)
references
References 52 publications
23
235
3
22
Order By: Relevance
“…Our study found that mesonephric carcinoma is characterized by a limited number of molecular aberrations that may be diagnostically useful and therapeutically important. The common mutations in mesonephric carcinoma are significantly different from those reported in other cervical and endometrial adenocarcinomas 19,20,28,29 and in the TCGA datasets by accessing the cBioPortal for Cancer Genomics, 30,31 (www.cbioportal.org). For example, KRAS/NRAS mutations are the most common molecular aberration detected in mesonephric carcinoma (81%); in contrast, these mutations are less common in other cervical and endometrial adenocarcinomas (less than 30%), [32][33][34] particularly in the microsatellite stable endometrioid adenocarcinomas and the serous endometrial carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that mesonephric carcinoma is characterized by a limited number of molecular aberrations that may be diagnostically useful and therapeutically important. The common mutations in mesonephric carcinoma are significantly different from those reported in other cervical and endometrial adenocarcinomas 19,20,28,29 and in the TCGA datasets by accessing the cBioPortal for Cancer Genomics, 30,31 (www.cbioportal.org). For example, KRAS/NRAS mutations are the most common molecular aberration detected in mesonephric carcinoma (81%); in contrast, these mutations are less common in other cervical and endometrial adenocarcinomas (less than 30%), [32][33][34] particularly in the microsatellite stable endometrioid adenocarcinomas and the serous endometrial carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a similar approach to the subclassification of high-grade endometrial carcinomas using mutational profiles did not generate a reliable multivariate logistic regression model. 13 This is possibly due to the lower discrimination of mutational data between types: that is, PI3K mutations are seen in endometrioid carcinoma FIGO grade 3 and serous carcinoma. It has also been shown that certain immunohistochemical markers such as PTEN 'outperform gene sequencing'.…”
Section: Modern Pathology (2013) 26 1594-1604mentioning
confidence: 99%
“…[10][11][12][13][14][15] The aim of this study was to assess specifically the interobserver agreement, recorded by gynecological pathologists from five academic centers across Canada, of histological type in high-grade endometrial carcinomas. A second aim was to correlate morphological diagnosis with a set of six routine immunohistochemical markers (TP53, CDKN2A (p16), ER, PGR, Ki67, and VIM) as well as a set of six experimental immunohistochemical markers (PTEN, ARID1A, CTNNB1, IGF2BP3, HNF1B, and TFF3).…”
mentioning
confidence: 99%
“…In addition, no PPP2R1B mutations were detected in our samples. The combined results of previous studies demonstrated that PPP2R1A mutations frequently occurred in breast, lung and endometrial carcinoma, as well as in OCCC and ovarian endometrioid carcinoma (5)(6)(7)(8)(9)(10)(11). Furthermore, the mutation frequencies of PPP2R1A in OCCC and ovarian endometrioid carcinoma patients were 4.1-9.1% (mean, 7.4%) and 10.0-12.2% (mean, 11.1%), respectively (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 76%
“…Subsequent studies confirmed this finding and also revealed frequent PPP2R1A mutations in patients with ovarian endometrioid carcinoma (6)(7)(8). Additionally, a high frequency of PPP2R1A mutations was also identified in several subtypes of endometrial carcinoma, with the highest frequency demonstrated in the serous subtype (6)(7)(8)(9). Furthermore, previous studies revealed that PPP2R1A mutations were present in patients with breast and lung malignancies, but absent in patients with (10,11), suggesting a general effect of PPP2R1A mutations on human cancer.…”
Section: Introductionmentioning
confidence: 63%